Multifaceted microglia during brain development: Models and tools - Bridlance, Cécile; Thion, Morgane Sonia (Frontiers in Neuroscience, 2023)
Microglia, the brain resident macrophages, are multifaceted glial cells that belong to the central nervous and immune systems. As part of the immune system, they mediate innate immune responses, regulate brain homeostasis and protect the brain in response to inflammation or injury. At the same time, they can perform a wide array of cellular functions that relate to the normal functioning of the brain. Importantly, microglia are key actors of brain development. Indeed, these early brain invaders originate outside of the central nervous system from yolk sac myeloid progenitors, and migrate into the neural folds during early embryogenesis. Before the generation of oligodendrocytes and astrocytes, microglia thus occupy a unique position, constituting the main glial population during early development and participating in a wide array of embryonic and postnatal processes. During this developmental time window, microglia display remarkable features, being highly heterogeneous in time, space, morphology and transcriptional states. Although tremendous progress has been made in our understanding of their ontogeny and roles, there are several limitations for the investigation of specific microglial functions as well as their heterogeneity during development. This review summarizes the current murine tools and models used in the field to study the development of these peculiar cells. In particular, we focus on the methodologies used to label and deplete microglia, monitor their behavior through live-imaging and also discuss the progress currently being made by the community to unravel microglial functions in brain development and disorders.